Expanding the host cell ubiquitylation machinery targeting cytosolic Salmonella. (7th August 2017) - Polajnar, Mira; Dietz, Marina S; Heilemann, Mike; Behrends, Christian
Abstract: Ubiquitylation is one of the cardinal post‐translational modifications in the cell, balancing several distinct biological processes and acting as a pathogen recognition receptor during bacterial pathogen invasion. A dense layer of polyubiquitin chains marks invading bacteria that gain access to the host cytosol for their selective clearance via xenophagy. However, the enzymes that mediate recognition of cytosolic bacteria and generate this ubiquitin (Ub) coat remain largely elusive. To address this, we employed an image‐based RNAi screening approach to monitor the loss of Ub on Salmonella upon depletion of human Ub E3 ligases in cells. Using this approach, we identified ARIH1 as one of the ligases involved in the formation of Ub coat on cytosolic bacteria. In addition, we provide evidence that the RING‐between‐RING ligase ARIH1, together with LRSAM1 and HOIP, forms part of a network of ligases that orchestrates recognition of intracellular Salmonella and participates in the activation of the host cell immune response. Synopsis: ARIH1 contributes to the formation of an ubiquitin coat on cytosolic S . Typhimurium. Together with LRSAM1 and HOIP, ARIH1 forms a network of E3 ligases that recognize cytosolic bacteria and mediate xenophagic degradation and host immune response. ARIH1 ubiquitylates cytosolic S . Typhimurium and contributes K48‐linked polyubiquitin chains to the bacterial ubiquitin coat. ARIH1 is recruited to S . Typhimurium where it colocalizes with LRSAM1. ARIH1 and LRSAM1 have xenophagy‐dependent and ‐independent functions. ARIH1 and LRSAM1 depletion is compensated by the recruitment of M1‐linked polyubiquitin chains to cytosolic bacteria. ARIH1, LRSAM1 and HOIP constitute a regulatory anti‐bacterial network. Abstract : ARIH1 contributes to the formation of an ubiquitin coat on cytosolic S . Typhimurium. Together with LRSAM1 and HOIP, ARIH1 forms a network of E3 ligases that recognize cytosolic bacteria and mediate xenophagic degradation and host immune response.